Improving Customer Loyalty Through Service Quality And Customer Satisfaction (A Study Conducted At Yani Salon, Demak) - Yani, Tri Endang (Economics and Business Solutions Journal, 2017)
This research is conducted due to the presence of business phenomena experienced by Yani Salon regarding to their customers complaints. The purpose of this research is to analyze the influence of dimensions of service quality on customer loyalty through customer satisfaction.The research samples are 96 respondents obtained using a purposive sampling method then followed with path analysis.The results show that the physical evidence, reliability, responsiveness, assurance, and empathy have positive and significant influence on customer satisfaction. Physical evidence and assurance do not have significant influence on customer loyalty, while reliability, responsiveness, and empathy have positive and significant influence on customer loyalty.